Structure and function of neurovascular unit in arterial hypertension - Kozniewska, Ewa; Aleksandrowicz, Marta (Frontiers in Molecular Neuroscience, 2026)
Arterial hypertension is considered a main risk factor for cognitive impairment and stroke. Although chronic hypertension leads to adaptive changes in the lager cerebral blood vessels which should protect the downstream microvessels, profound changes in the structure and function of cerebral microcirculation were reported in this disease. The structural changes lead to dysregulation of the neurovascular unit and manifest themselves in particular as endothelial dysfunction, disruption of the blood-brain barrier and impairment of neurovascular coupling. The impairment of neurovascular coupling results in inadequate functional hyperemia, which in turn may lead to cognitive decline and dementia. In this review the effects of chronic arterial hypertension on the essential components of neurovascular unit involved in neurovascular coupling such as endothelial cells, astrocytes and pericytes are discussed.